Studi Stabilitas Sediaan Suspensi Obat dalam Kondisi Suhu yang Berbeda - Muhammad Fadhli; M. Chaidir Hafidz; Nor Latifah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Stability testing is an important step in the development of pharmaceutical products. This testing must be conducted before the product is manufactured, whether on an industrial or non-industrial scale. Currently, liquid formulations are experiencing rapid development, one of which is suspension. Suspension itself is a liquid formulation that contains undissolved solid particles dispersed in the liquid phase. To assess the stability of suspension, various evaluations are performed such as organoleptic tests, sedimentation volume, redispersion, density, viscosity, particle size distribution, and pH measurement. Based on several studies, temperature is known to affect the stability of drugs, especially in suspension formulations. A study related to diclofenac suspension showed that at a temperature of 4°C, its stability reaches 96.3%, while at temperatures of 40°C and 60°C, there is a significant reduction in content, amounting to 89.58% and 85.17% respectively. Meanwhile, research on folic acid suspension revealed that the drug remains stable at temperatures of 4°C and 25°C, although on day 90 there was an increase in pH. Another study on cefuroxime axetil suspension showed that at a temperature of 20°C, its concentration was 87.68%, while at 5°C, it was higher at 92.35%. This research underscores the importance of considering temperature in the storage and formulation of pharmaceutical suspensions to maintain their effectiveness and stability.